(untitled) (Journal of Special Education and Rehabilitation, 2013)
Probably from the very beginning of the human curiosity in disability features for family’s values, structures, parenting styles, circles of support, strengths and others, have been just as appealing as the child or adult with disabilities themselves. As many studies confirmed, professionals’ approach to parents, getting adequate information and type of treatment present a challenge to families of children with established developmental disabilities and those at risk for disability. The main purpose of this study was to analyze parents’ satisfaction with these three main features of support in early treatment of their child with intellectual disability. The sample consisted of 81 families with intellectually disabled child, recruited from seven types of care provided in three towns in Croatia. Data were analyzed with one-way ANOVA comparing variety of parents satisfaction in four groups formed according to the level of intellectual disability. The method revealed a significant difference among groups in the variable referring to the parents satisfaction with treatment accessibility and its frequency provided.